Azulejo blues – an analytical study of the blue colours in portuguese azulejos - Fares, M. (2012)
This communication reviews the main variants of the blue colour found on glazed tiles (mainly of Portuguese manufacture) used in Portugal from the 16th to the late 18th centuries and discusses the composition of the pigments from which they result.